2011
DOI: 10.1261/rna.2837311
|View full text |Cite
|
Sign up to set email alerts
|

The role of the 5′–3′ exoribonuclease XRNA in transcriptome-wide mRNA degradation

Abstract: The steady-state level of each mRNA in a cell is a balance between synthesis and degradation. Here, we use high-throughput RNA sequencing (RNASeq) to determine the relationship between mRNA degradation and mRNA abundance on a transcriptome-wide scale. The model organism used was the bloodstream form of Trypanosoma brucei, a protist that lacks regulation of RNA polymerase II initiation. The mRNA half-lives varied over two orders of magnitude, with a median half-life of 13 min for total (rRNA-depleted) mRNA. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 64 publications
4
92
0
Order By: Relevance
“…1) are listed in Table 1. The proportion of SL signal that remained after 30-min transcription inhibition in wildtype cells was 50%-60% (Table 1), which was approximately in agreement with our previous estimates based on the abundances of individual mRNAs (Haanstra et al 2008;Manful et al 2011). Supplemental Figure S1A shows the time course of disappearance of SL signal over a 2-h time course.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1) are listed in Table 1. The proportion of SL signal that remained after 30-min transcription inhibition in wildtype cells was 50%-60% (Table 1), which was approximately in agreement with our previous estimates based on the abundances of individual mRNAs (Haanstra et al 2008;Manful et al 2011). Supplemental Figure S1A shows the time course of disappearance of SL signal over a 2-h time course.…”
Section: Resultssupporting
confidence: 91%
“…Transcriptome-wide analysis of trypanosome mRNA halflives in cells after XRNA RNAi demonstrated that XRNA depletion inhibited the degradation of unstable mRNAs, while some of the more stable mRNAs had shorter halflives (Manful et al 2011). We have now extended this to all the known factors involved in degradation from the 3 ′ end: PAN2, the exosome, and components of the CAF1/NOT complex.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations